Improvement Of Motivation With Leadership And Work Environment And The Impact Of Work Satisfaction - Oka Martini , Ida Ayu (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
This research was conducted to analyze the role of leadership, work environment, and work motivation in increasing satisfaction a nurse's job at the Ganesha General Hospital. The number of nurses in the hospital was 135. Data collection was carried out by distributing questionnaires to research respondents namely all nurses totalling 35 nurses so that it included the saturated sample method. Data analysis techniques were performed using path analysis, hypothesis testing was performed at a significance level of 5 per cent. Data processing is done using computer applications. The results showed that work motivation, leadership and work environment were positively significantly able to increase nurse job satisfaction. Work motivation acts as a partial mediator in the relationship of leadership to job satisfaction and works environment to job satisfaction.